A Refinement of Jensen’s and Minkowski’s Inequalities via Superquadratic Functions - Anton Asare-Tuah; Edward Prempeh (International Journal of Mathematics and Mathematical Sciences)
We provide in this note a different refinement of Jensen’s inequality obtained via superquadratic functions. A refinement of Minkowski’s and Hölder’s inequalities is also established as an application of our refined Jensen’s inequality.